Respuesta :
To find the length of the playground, you multiply length(width) = area
To reverse this, you have to divide on each side by the term we know (x + 3)
The answer would be width = (x³ - 7x + 6) / (x + 3)
If you need help solving this, let me know
To reverse this, you have to divide on each side by the term we know (x + 3)
The answer would be width = (x³ - 7x + 6) / (x + 3)
If you need help solving this, let me know
Answer:
Length is : [tex]x^{2} -3x+2[/tex]
Step-by-step explanation:
The width of the rectangular playground is given as = x+3
The area of the playground is given as = [tex]x^{3} -7x+6[/tex]
We have to find the length.
The area of the rectangle is given as :
[tex]A= length*width[/tex]
So, length can be found as : [tex]length=\frac{area}{width}[/tex]
=> [tex]\frac{x^{3}-7x+6 }{x+3}[/tex]
Solving this we get,
Factoring [tex]\frac{x^{3}-7x+6 }[/tex] we get (x-1)(x-2)(x+3)
Using the rational root theorem and assuming a0=6 and a(n)=1
Divisors of a0 = 1,2,3,6
Divisor of a(n) = 1
1/1 is the root of equation. So, factoring out x-1 we get
[tex](x-1)\frac{x^{3}-7x+6 }{x-1}[/tex]
[tex]\frac{x^{3}-7x+6 }{x-1}[/tex]
[tex]x^{2} +\frac{x^{2}-7x+6 }{x-1}[/tex]
[tex]x^{2} +x+\frac{-6x+6}{x-1}[/tex]
dividing [tex]\frac{-6x+6}{x-1}[/tex] we get -6
So, result becomes [tex]x^{2} +x-6[/tex]
Factoring this we get: [tex](x-2)(x+3)[/tex]
[tex]\frac{(x-1)(x-2)(x+3)}{(x+3)}[/tex]
Cancelling x+3
We get the length as = [tex](x-1)(x-2)[/tex] or [tex]x^{2} -3x+2[/tex]